Sex and the facilitation of cued fear by prior contextual fear conditioning in rats - Vazquez, Katherine; Cole, Kehinde E.; Parsons, Ryan G. (Learning & memory (Cold Spring Harbor, N.Y.), 2024)
Previous studies have shown that the formation of new memories can be influenced by prior experience. This includes work using Pavlovian fear conditioning in rodents that has shown that an initial fear conditioning experience can become associated with and facilitate the acquisition of new fear memories, especially when they occur close together in time. However, most of the prior studies used only males as subjects, resulting in questions about the generalizability of the findings from this work. Here we tested whether prior contextual fear conditioning would facilitate later learning of cued fear conditioning in both male and female rats, and if there were differences based on the interval between the two conditioning episodes. Our results showed that levels of cued fear were not influenced by prior contextual fear conditioning or by the interval between training; however, females showed lower levels of cued fear. Freezing behavior in the initial training context differed by sex, with females showing lower levels of contextual fear, and by the type of initial training, with rats given delayed shock showing higher levels of fear than rats given immediate shock during contextual fear conditioning. These results indicate that contextual fear conditioning does not prime subsequent cued fear conditioning and that female rats express lower levels of cued and contextual fear conditioning than males.